The oxidation behavior of a Ni2FeCoCrAl0.5 high-entropy superalloy in O2-containing environments. (September 2019) - Kai, W.; Cheng, F.P.; Chien, F.C.; Lin, Y.R.; Chen, D.; Kai, J.J.; Liu, C.T.; Wang, C.J.
Highlights: The oxidation of the Ni2 FeCoCrAl0.5 high-entropy superpalloy was studied in O2 -containing environments at 900 °C. The oxidation kinetics of the superalloy followed the parabolic-rate law at PO2 < 2.1 × 10 4 Pa. The scales formed on the superalloy depended on oxygen pressure. Abstract: The oxidation behavior of a Ni2 FeCoCrAl0.5 high-entropy superalloy was studied at 900 °C in O2 -containing environments over the oxygen pressure range of 10 - 1.0 × 10 5 Pa. The superalloy oxidized parabolically at PO2 < 2.1 × 10 4 Pa, having its oxidation rates increasing with increasing oxygen pressure. An exclusive α-Al2 O3 layer formed on the alloy with its thickness increased with oxygen pressure. On the contrast, a mass-lost kinetics was observed and heterophasic scales of intermixed α-Al2 O3, Cr2 O3, and M-Cr spinels (M = Ni, Fe, or Co) were detected at PO2  = 1.0 × 10 5 Pa.